Generation of Multicomponent Molecular Cages using Simultaneous Dynamic Covalent Reactions. Issue 71 (23rd November 2017) - Drożdż, Wojciech; Bouillon, Camille; Kotras, Clément; Richeter, Sébastien; Barboiu, Mihail; Clément, Sébastien; Stefankiewicz, Artur R.; Ulrich, Sébastien
Abstract: Cage compounds are very attractive structures for a wide range of applications and there is ongoing interest in finding effective ways to access such kinds of complex structures, particularly those possessing dynamic adaptive features. Here we report the accessible synthesis of new type of organic cage architectures, possessing two different dynamic bonds within one structure: hydrazones and disulfides. Implementation of three distinct functional groups (thiols, aldehydes and hydrazides) in the structure of two simple building blocks resulted in their spontaneous and selective self‐assembly into aromatic cage‐type architectures. These organic cages contain up to ten components linked together by twelve reversible covalent bonds. The advantage provided by the presented approach is that these cage structures can adaptively self‐sort from a complex virtual mixture of polymers or macrocycles and that dynamic covalent chemistry enables their deliberate disassembly through controlled component exchange. Abstract : Doing some remodelling : Multi‐component aromatic cages are self‐assembled, self‐sorted, and reconfigured in aqueous solutions through two simultaneous dynamic covalent reactions, hydrazone and disulfide.